THE INTEGRATION OF THIRD-COUNTRY NATIONALS IN THE LATVIAN EDUCATION ENVIRONMENT: THE CURRENT SITUATION AND KEY ISSUES - Jurgena, Inese; Keviša, Ingrīda; Līduma, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Due to the European migrant crisis, the issue concerning the integration of refugees, third-country nationals, into Latvia’s society has become increasingly topical in the last years. Since a lot of refugees are under 18, schools also must be ready to accept learners of other nationalities and cultures and help them integrate into the community of the host country. According to studies conducted in Latvia, the system of education needs to change the attitude towards the integration of immigrants in the school environment. Therefore, the incorporation of inter-cultural experience in the curricula of teacher-training institutions is a significant factor that could enable pre-service teachers to prepare for their professional life and the implementation of the approach of inclusive education at school. The aim of the article is to analyse the current situation and the main issues concerning the integration of the children of third-country nationals in the Latvian school environment and the multi-cultural Latvian society. The study is based on the analysis of scientific literature, documents, academic research data as well as student essays. Having analysed the opinions of 166 respondents, the authors of the article concluded that it is important to promote the development of a positive attitude to the inclusion of third-country nationals in the Latvian education environment in the process of teacher training, focussing on cross-cultural communication and the principles of inclusive education.